The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1038/scsandc.2016.34
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of supraspinal control of leg movement in a chronic complete flaccid paraplegic man after continuous low-frequency pelvic nerve stimulation and FES-assisted training

Abstract: INTRODUCTION:More than 30 years ago, functional electrical stimulation (FES) was developed as an orthotic system to be used for rehabilitation for SCI patients. In the present case report, FES-assisted training was combined with continuous low-frequency stimulation of the pelvic somatic nerves in a SCI patient. CASE PRESENTATION: We report on unexpected findings in a 41-year-old man with chronic complete flaccid paraplegia, since he was 18 years old, who underwent spinal stem cell therapy and a laparoscopic im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Indeed, whereas a number of neurorehabilitation protocols have induced some level of neurological recovery in motor incomplete SCI patients (AIS C/D) (including stepping training [22,23], operant conditioning [24,25] or functional electrical stimulation [26]), improvement in motor complete SCI has been principally observed through compensatory mechanisms [15]. Only recently, a few studies in rats [27] and humans [28] have shown partial motor recovery (neurological and functional) in severe cases of SCI, following training with invasive epidural stimulation (see [29] for a review) or invasive pelvic nerve stimulation [30]. Notably, clinical improvement was noticed when such invasive stimulation was paired with direct patient control of the stimulating system, via a brain-machine interface [31] (see [32] for a review).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, whereas a number of neurorehabilitation protocols have induced some level of neurological recovery in motor incomplete SCI patients (AIS C/D) (including stepping training [22,23], operant conditioning [24,25] or functional electrical stimulation [26]), improvement in motor complete SCI has been principally observed through compensatory mechanisms [15]. Only recently, a few studies in rats [27] and humans [28] have shown partial motor recovery (neurological and functional) in severe cases of SCI, following training with invasive epidural stimulation (see [29] for a review) or invasive pelvic nerve stimulation [30]. Notably, clinical improvement was noticed when such invasive stimulation was paired with direct patient control of the stimulating system, via a brain-machine interface [31] (see [32] for a review).…”
Section: Introductionmentioning
confidence: 99%
“…Neuropelveology has a wide scope of application to pelvic conditions including neuropelveological evaluation to chronic pelvic pain, vascular entrapment syndrome as well as the use of implantation of electrode for pelvic visceral dysfunction and even implantation of electrodes to pelvic nerve for assisting ambulation in patient with spinal cord injury. [ 16 ] In addition to this specialized knowledge, it also requires a high degree of laparoscopic surgical skill.…”
Section: Discussionmentioning
confidence: 99%
“…The crucial discovery we made with the LION procedure in people with SCI was undoubtedly the fact that some patients experienced enough recovery of supra-spinal control for some leg movement or even standing and walking [ 26 , 29 ]. In the most recent study of 29 patients with SCI 10 years after a LION procedure, 20 of them (71.4%) were able to demonstrate an electrically assisted, voluntary extension of the knee [ 30 ] ( Figure 10 ).…”
Section: Lion Proceduresmentioning
confidence: 99%